(untitled) (Journal of actual problems of jurisprudence, 2023)
In this article, the author examines the problems of ensuring the rule of law in the political and legal views of Zhakhansha Dosmukhamedov and the works of the Alash intelligentsia. This article has been prepared on the basis of long-term studies of materials in the archives of the Republic of Kazakhstan, as well as in the archives of major cities of the Russian Federation and the Republic of Uzbekistan. Also, the basis of this work were new archival documents collected as part of the work of the State Commission for the Full Legal and Political Rehabilitation of Victims of Political Repression, formed by Decree of the President of the Republic of Kazakhstan Kassym-Jomart Tokayev. Zhakhansha Dosmukhamedov, as one of the leaders who headed the western branch of AlashOrda and a professional lawyer, as well as a prominent politician of the early twentieth century, made a significant contribution to the development of law in the territory of the Kazakh territory and his political and legal views are of interest to modern legal science. The appeal to the heritage of “Alash” is an urgent and most developed topic, since our country is on the way to building a New Kazakhstan today. Therefore, the issues of ensuring the rule of law and the administration of justice are becoming a necessary mechanism in the protection of human rights and the development of a democratic society. Key words: law, politics, repression, Soviet power, independence, Alash.